METAPHOR AND METONYMY IN COSTUME DESIGN TERMINOLOGY: A COGNITIVE-SEMANTIC APPROACH (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The language of costume design is an intricate system where creativity, culture, and cognition intersect. This article explores the role of metaphor and metonymy in shaping the terminology of costume design, emphasizing their cognitive, semiotic, and pedagogical significance. Metaphor and metonymy are not mere stylistic ornaments but fundamental linguistic mechanisms that structure conceptualization in design discourse. They enable designers to translate abstract aesthetic visions into material forms and communicate cultural meanings effectively. The study reveals how figurative thinking supports innovation, aids professional communication, and reflects historical and cultural transformations in fashion. Understanding these mechanisms contributes to a deeper comprehension of the interdisciplinary nature of costume design vocabulary and its pedagogical application in multilingual education.